The Visitor Perception for Vegetation and The Existence of City Park, Tebing City, North Sumatra, Indonesia - Arinah, Hafizah; Syahputra, Orang Kaya Hasnanda; Fadhilla, Suri; Andayani, Wahyu; Sari, Ratna; Setiawan, Jajang (Fakultas Kehutanan Universitas Mulawarman, 2026)
One type of green open space crucial to creating a delightful, comfortable, and healthy urban environment for city dwellers is Tebing Tinggi City Park. This study aims to examine how tourists see the presence of City Park Tebing Tinggi City and its greenery. To conduct research, two steps must be completed: creating a study questionnaire and interviewing park visitors in Tebing Tinggi City Park. The generated data will be tallied, graphically represented, and subjected to qualitative analysis through descriptions. The socio-demographic traits and perceptions of the respondents were investigated using descriptive analysis. According to the observation findings, visitors' perceptions of Tebing Tinggi City Park are also adequate or good. These impressions encompass the park's easy accessibility, active functions and activities, comfort and impression quality, and social capacity for teamwork. Then, we discovered that most people had a positive opinion of vegetation, with 70% of respondents thinking that it has more positive effects on animals, shade, and air quality than negative ones.